2021
DOI: 10.3390/sym13060938
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Red Blood Cell Rigidity from Sequence Data of Blood Flow Simulations Using Neural Networks

Abstract: Numerical models for the flow of blood and other fluids can be used to design and optimize microfluidic devices computationally and thus to save time and resources needed for production, testing, and redesigning of the physical microfluidic devices. Like biological experiments, computer simulations have their limitations. Data from both the biological and the computational experiments can be processed by machine learning methods to obtain new insights which then can be used for the optimization of the microflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Our recent research goal is therefore not to compare the consistency of real and simulation experiments, but to focus on the differences in the capabilities of 3D models and their, video-recording-based, 2D descriptions. In [17], we showed that different results can be yielded by whether the video footage was acquired at the top or at the side of a channel with a flowing fluid.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our recent research goal is therefore not to compare the consistency of real and simulation experiments, but to focus on the differences in the capabilities of 3D models and their, video-recording-based, 2D descriptions. In [17], we showed that different results can be yielded by whether the video footage was acquired at the top or at the side of a channel with a flowing fluid.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors influence the migration of particles across streams in confined-space flow suspensions, with reduced elasticity of a certain fraction of cells generally considered to be a key factor. In a previous study by [17], we worked with only two levels of elasticity of RBCs, healthy and damaged (stiffer). In the present work, RBCs with three and nine elasticity levels, respectively, are included in the individual simulations, which both represents a shift towards a more realistic model of blood flow and creates the need to address the issue from a more holistic perspective.…”
Section: Simulation Model and Input Settingsmentioning
confidence: 99%
See 2 more Smart Citations
“…The determination of RBC elasticity through simulation experiments has been investigated in prior works [16,17]. However, this paper proposes a novel approach capable of identifying various levels of RBC elasticity associated with different diseases from video recordings.…”
Section: Introductionmentioning
confidence: 99%